2004
DOI: 10.4028/www.scientific.net/jmnm.20-21.494
|View full text |Cite
|
Sign up to set email alerts
|

Electron Structure, Stability and Nanocrystallization of Al - Based Amorphous Alloys

Abstract: Electron transport studies of Al-based alloys show that the strong bonds between Al-TM and Al-Y atoms arise by mixing of 3d and 4d electron states of TM and Y atoms with the 3s and 3p states from Al. Thermal stability of the Al-RE alloys is controlled by the low diffusity of heavy RE atoms. The results allow to optimize preparation conditions for nanocrystallizing Al-based alloys with enhanced mechanical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…The electrical resistivity was measured in a range 300-800 K by DC four-probe method with accuracy of 0.01%. The thermoelectric power was measured by differential method [5,6]. The heating rate during both the measurements was 10 K/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrical resistivity was measured in a range 300-800 K by DC four-probe method with accuracy of 0.01%. The thermoelectric power was measured by differential method [5,6]. The heating rate during both the measurements was 10 K/min.…”
Section: Methodsmentioning
confidence: 99%
“…The enhanced threshold crystallization temperatures T x , revealing the relatively higher stability of amorphous phase, are found in alloys with raising Ni content. Such a tendency is probably due to the bonding interaction between Al and Ni atoms, which refrain an rearrangement of amorphous matrix leading thus to nanocrystallization [1,5]. …”
Section: Amorphous Statementioning
confidence: 99%
“…It was observed that thermoelectric power of QCs varies strongly and nonsystematically even at small changes of the Fermi energy occurring due to the composition variation [18]. Electrical resistivity and thermoelectric power (TEP) measurements are very sensitive experimental techniques which can be successfully applied to analysis of crystallization of metallic glasses [19][20][21]. In this study we apply those methods to investigate quasicrystal-forming Zr 70 Pd 30 amorphous alloy.…”
Section: Introductionmentioning
confidence: 97%